ANALISIS PROSES PEMUNGUTAN DAN PERHITUNGAN PAJAK BPHTB SEBAGAI SALAH SATU SUMBER PENDAPATAN ASLI DAERAH (STUDI PADA DAERAH KABUPATEN SUMBAWA) - EMILIA EMILIA; AHMAD YAMIN; SUPARMAN SUPARMAN (GANEC SWARA, 2024)
The aim of this research is to explain the process of collecting and calculating land and building rights acquisition tax (BPHTB) in the Sumbawa Regency area. This research uses qualitative methods, with an interpretive descriptive approach. There were 5 informants for this research. Then, the data collection techniques used were documentation and interviews. Then the analysis technique used is data reduction and data presentation. The results of this research are that BPHTB revenues have increased and exceeded the targets set by the Sumbawa Regency Regional Revenue Agency. Obstacles in collecting BPHTB tax are from the Taxpayer, Human Resources, lack of information and communication about regional taxation to the community, many transactions in Sumbawa Regency are still under NJOPTKP so that BPHTB tax payments are nil, national influence (sluggish level of property buying and selling in the community) Furthermore, there was an increase in the BPHTB tax contribution from 2019-2021 and decreased in 2022. In detail, in 2019 the realization was Rp. 2,201,502,827.00 with a target of Rp. 4,000,000,000.00, while in 2020 the realization reached Rp. 5,895,852,816.00, with a target of Rp. 4,700,000,000. Furthermore, in 2021 the realization was IDR. 4,180,093,825.00, with a target of Rp. 4,000,000,000, and in 2022 the realization was Rp. 10,015,983,797.00 with a target of Rp. 8,240,000,000.00.